A Comparative Study of Syrian Immigrants in Gender Equality Discourse and Integration in the UK and Sweden - Mahayasa, Dias Pabyantara Swandita; Buldhani, Salma Kinanti (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2025)
A significant number of migrants arrived in Europe in 2015, with Syrian refugees accounting for a disproportionate share of these new arrivals. Syria has a poor level of gender equality compared to other European countries such as Sweden and the UK. With an emphasis on the disparities in gender norms between their native country and host nation, this study aims to examine the phenomena of gender discourse and the integration challenges Syrian populations face. Strong patriarchal beliefs in Syrian communities make integration complicated and fuel many discussions about gender roles in these groups. This research uses a comparative method to analyze the gender equality discourse and integration experiences of Syrian refugees in the UK and Sweden. Through policy analysis and secondary data from journal articles, the research investigates how gender equality is perceived, communicated, and implemented within Syrian immigrant communities and the broader societal frameworks of both countries. The study reveals distinct national approaches to gender equality and integration, highlighting the impact of these differences on the lived experiences of Syrian men and women.